PENGARUH STRES KERJA TERHADAP TURNOVER INTENTIONS YANG DIMEDIASI OLEH BURNOUT” (STUDI PADA KARYAWAN HOTEL BINTANG 4 (EMPAT) DI KOTA MATARAM) - isra dewi kuntary ibrahim (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
Companies are required to maintain the employees by paying attention on the occurrence of turnover intention before the end of turnover. This research is aimed at detrmining and analyzing the significant effect of work stresses on the turnover intention, the significant effect of burnout on the turnover intentions, the significant effect of work stress on turnover intentions with burnout as the mediating variable at the employees of four star hotels in Mataram. This research is associative-causality study witf primary and secondary data. The data were collected through interview, documentations, and questionnaires. The population are all employees of the operational department; front office, food and beverage service, food and beverage product, housekeeping, and engineering of the four star hotels in Mataram. All of the them are 333 employees. The samples were selected though Slovin formula that took 182 resmpondents obtained from the stratified random sampling. The data were analyzed with PLS. The research showed that work stress has positive but not significant effect on the turnover intentions, work stress has positive and significant effect on the turnover intentions, work stress has positive and significant effect on the burnout, burnout has positive and significant effect on turnover intentions, work stress has positive and significant effect on the turnover intentions with burnout as the mediating variable. The Implication of this research for companies is that the companies need to maintain the work stress to the optimum level to get the positive effect for the company and to make sense of responsibility of employees, to provide program to support the spirit of work for employees by giving more space for the creativity of the employees to avoid monotonous work.  Kata Kunci : Work Stress, Burnout, Turnover Intentions, Hospitality Industry, Patial Least Square (PLS).